2018
DOI: 10.1055/a-0802-9175
|View full text |Cite
|
Sign up to set email alerts
|

Peak Oxygen Uptake in Chronic Fatigue Syndrome/Myalgic Encephalomyelitis: A Meta-Analysis

Abstract: To evaluate the magnitude of the difference in VO2peak between patients with Chronic Fatigue Syndrome/ Myalgic Encephalomyelitis (CFS/ME) and apparently healthy controls, 7 databases (Cochrane, PubMed, PsycINFO, Web of Knowledge, Embase, Scopus, Medline) were searched for articles published up to March 2018. Search terms included “chronic fatigue syndrom*”AND (“peak” OR “maxim*” OR “max”) AND (“oxygen uptake” OR “oxygen consumption” OR “VO2peak” or “VO2max”. Eligibility criteria were adults>18 y with clinic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 58 publications
0
25
0
Order By: Relevance
“…Phys F: Physical Functioning scale of the SF-36 questionnaire; %peak VO 2 : peak VO 2 oxygen uptake relative to controls [37]; No of steps: number of steps per day functioning scale of 0.91 [44], suggesting that the use of the physical functioning score is valid with an acceptable sensitivity and specificity. Several studies have shown a decreased peak VO 2 in ME/CFS patients [45]. However, only one study determined the relation between the peak VO 2 and accelerometer data in female ME/CFS patients: higher peak VO 2 values were related to a higher physical activity time, physical activity energy expenditure, and a mean energy expenditure [46].…”
Section: Discussionmentioning
confidence: 98%
“…Phys F: Physical Functioning scale of the SF-36 questionnaire; %peak VO 2 : peak VO 2 oxygen uptake relative to controls [37]; No of steps: number of steps per day functioning scale of 0.91 [44], suggesting that the use of the physical functioning score is valid with an acceptable sensitivity and specificity. Several studies have shown a decreased peak VO 2 in ME/CFS patients [45]. However, only one study determined the relation between the peak VO 2 and accelerometer data in female ME/CFS patients: higher peak VO 2 values were related to a higher physical activity time, physical activity energy expenditure, and a mean energy expenditure [46].…”
Section: Discussionmentioning
confidence: 98%
“…Current research shows disparity when comparing individuals with ME/CFS to those who are healthy controls, with some indicating that healthy controls have a higher peak VO 2 compared to those with ME/CFS and others whom indicate that those with ME/CFS have a peak VO 2, which is similar to those who are healthy controls . In spite of this, a recent meta‐analysis compared the data of healthy controls and those with ME/CFS from a single exercise test. Franklin et al demonstrated a pooled mean VO 2 peak that was 5.2 mL kg −1 min −1 lower in ME/CFS compared with healthy controls .…”
Section: Introductionmentioning
confidence: 99%
“…In spite of this, a recent meta‐analysis compared the data of healthy controls and those with ME/CFS from a single exercise test. Franklin et al demonstrated a pooled mean VO 2 peak that was 5.2 mL kg −1 min −1 lower in ME/CFS compared with healthy controls . However, between subject variability was 3.5 (1.5‐4.5 mL kg −1 min −1 ) indicating substantial heterogeneity.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have shown a decreased peak VO 2 in ME/CFS patients [46]. However, only one study determined the relation between the peak VO 2 and accelerometer data in female ME/CFS patients: higher peak VO 2 values were related to a higher physical activity time, physical activity energy expenditure, and a mean energy expenditure [47].…”
Section: Discussionmentioning
confidence: 98%